Asymmetric Neutral‐alkaline Microbial Electrolysis Cells for Hydrogen Production. Issue 7 (3rd April 2022) - Dai, Ling; Xiang, Lijuan; Zhang, Mengtian; Wen, Zhenhai; Xu, Qiuhua; Chen, Kai; Zhao, Zhifeng; Ci, Suqin
Abstract: The development of highly efficient cathodes for hydrogen production that can operate in a suitable pH condition is a daunting challenge in microbial electrolysis cells (MECs). Herein, an asymmetric neutral‐alkaline double‐chamber microbial electrolysis cells (AMECs) by using conventional carbon brush with microorganism attached as neutral anode and the Ru/CNTs electrode as alkaline cathode, respectively, was proposed. To implement this, a hybrid with ruthenium nanoparticles loaded on conductive carbon nanotubes (Ru/CNTs) was prepared by a reduction deposition method, which exhibited comparable electrocatalytic performance to the expensive benchmark Pt/C catalysts for hydrogen evolution reaction (HER). Compared to the traditional MECs running in symmetric neutral electrolyte, the as‐developed AMEC displayed a higher current density of 17.13 A m −2 and hydrogen production rate of 0.167 m 3 m −2 d −1 . The present AMEC provides an energy‐saving and cost‐effective process technology for electrolysis H2 generation. Abstract : Energy saving : Ru0.12 CNTs was obtained using a reduction deposition method. It could reach a current density of 10 mA cm −2 at an overpotential of only 31 mV in HER under alkaline conditions, exceeding that of Pt/C. When applied to an innovative asymmetric neutral‐alkaline microbial electrolysis cell (AMEC), Ru0.12 CNTs‐AMEC produced hydrogen efficiently.